2013
DOI: 10.1109/tns.2013.2278624
|View full text |Cite
|
Sign up to set email alerts
|

Bias Atlases for Segmentation-Based PET Attenuation Correction Using PET-CT and MR

Abstract: This study was to obtain voxel-wise PET accuracy and precision using tissue-segmentation for attenuation correction. We applied multiple thresholds to the CTs of 23 patients to classify tissues. For six of the 23 patients, MR images were also acquired. The MR fat/in-phase ratio images were used for fat segmentation. Segmented tissue classes were used to create attenuation maps, which were used for attenuation correction in PET reconstruction. PET bias images were then computed using the PET reconstructed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 33 publications
(41 reference statements)
4
54
0
Order By: Relevance
“…In one example demonstrated by Samarin et al, (32) classifying bone as soft tissue resulted in less than 6% difference for PET voxels in the heart region. Ouyang et al (33) also concluded that three‐class segmentation can be sufficient for PET quantification in the heart, as it yields less than 5% quantification difference after compensation. These studies indicate that bone segmentation may not be necessary for cardiac PET/MR.…”
Section: Discussionmentioning
confidence: 99%
“…In one example demonstrated by Samarin et al, (32) classifying bone as soft tissue resulted in less than 6% difference for PET voxels in the heart region. Ouyang et al (33) also concluded that three‐class segmentation can be sufficient for PET quantification in the heart, as it yields less than 5% quantification difference after compensation. These studies indicate that bone segmentation may not be necessary for cardiac PET/MR.…”
Section: Discussionmentioning
confidence: 99%
“…and to assign a single value to each class. Using discretized attenuation values for μ-maps instead of a continuous attenuation image was evaluated in [28,29] and the accuracy of reconstructed images is dependent on locations. It was claimed that it is feasible to use discretized μ-maps clinically.…”
Section: Sources Of Attenuation/scatter Informationmentioning
confidence: 99%
“…It was claimed that it is feasible to use discretized μ-maps clinically. Segmentation is performed on T1-weighted or T2-weighted MR images [29,85,86] or on ultrashort echo time (UTE) sequence MR images for better imaging bones with very short T 2 values [87,88]. The other is to use atlasbased methods with machine learning techniques [27,89].…”
Section: Sources Of Attenuation/scatter Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve reliable PET quantification, MR images should ideally be segmented into 6 tissue classes, namely, soft-tissue, fat, lung, air, cortical and spongeous bones (Ouyang et al, 2013, Akbarzadeh et al, 2013a). However, a major challenge is the differentiation between bones and air cavities in the skull and surrounding soft-tissue in the vertebra, since bones do not exhibit detectable signals when using conventional MRI sequences mainly due to their short T2 relaxation time.…”
Section: Introductionmentioning
confidence: 99%